2019
DOI: 10.3224/ijree.v7i1.06
|View full text |Cite
|
Sign up to set email alerts
|

The After-School Program Collaboration Quality Index (CQI): Results of a Validation Study

Abstract: There has been a surge in the demand for the establishment of high-quality after-school programs (ASP) predicated on professional collaboration between in-school and after-school educators (OECD, 2014). In this validation study, we outline the psychometric properties of the Collaboration Quality Index (CQI) comprised of four predominant scales, using data collected from 44 Swiss ASPs and 266 ASP staff members. Internal and external validity findings, as well as bivariate correlations, indicated that the CQI is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Despite the relevance of IPC in child centres, Keuning et al (2022) concluded that IPC is still often short-term oriented, occurs on a small scale and is characterised by low levels of cohesion. Moreover, OSC occupies a vulnerable position within IPC, manifested by the fact that in many countries OSC receives little priority and faces low status (Cartmel, 2019;Hurst, 2020;Jutzi and Woodland, 2019). Yet, it is specifically between school and OSC that one would expect frequent IPC, given that children experience boundary crossing from school to OSC daily.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relevance of IPC in child centres, Keuning et al (2022) concluded that IPC is still often short-term oriented, occurs on a small scale and is characterised by low levels of cohesion. Moreover, OSC occupies a vulnerable position within IPC, manifested by the fact that in many countries OSC receives little priority and faces low status (Cartmel, 2019;Hurst, 2020;Jutzi and Woodland, 2019). Yet, it is specifically between school and OSC that one would expect frequent IPC, given that children experience boundary crossing from school to OSC daily.…”
Section: Introductionmentioning
confidence: 99%